Targeting oxidized phosphatidylcholines in SOD1-associated ALS: therapeutic potential of PC-OxPL-VecTab® - Andreia Gomes-Duarte; Sofia Pascoal; Rob Haselberg; Marina Sogorb-Gonzalez; Sander van Deventer (Frontiers in Neuroscience, 2025)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by progressive motor neuron degeneration. Mutations in the superoxide dismutase 1 (SOD1) gene account for a significant fraction of familial ALS (fALS) cases. Oxidative stress and oxidized phosphatidylcholines (PC-OxPL) contribute to neuroinflammation and neuronal damage, and to motor neuron degeneration in ALS. We previously demonstrated the therapeutic efficacy of an AAV-delivered anti-PC-OxPL single-chain variable fragment (PC-OxPL-VecTab®) in neutralizing PC-OxPL toxicity in the periphery and central nervous system (CNS), but the therapeutic potential of PC-OxPL-VecTab® has not been investigated in the context of fALS and SOD1-associated ALS. We report that PC-OxPL accumulation contributes to the pathological phenotypes associated with SOD1G93A iPSC-derived motor neurons and the corresponding mouse model. The current findings further demonstrate that PC-OxPL-VecTab® is efficacious in neutralizing the downstream effects of SOD1-associated PC-OxPL accumulation, such as altered gene expression and axonal health in SOD1 motor neurons, as well as a pathological lipid profile in the SOD1G93A mouse model. Collectively, the present study underscores the significance of PC-OxPL dysfunction in the context of SOD1 genotypes and sheds light on the potential of PC-OxPL-VecTab® for therapeutically targeting ALS.